Introducing Linguistic Morphology - Bauer, Laurie (Edinburgh University Press, 2003)
An expanded and updated new edition of this best-selling introduction to linguistic morphology. The text guides the reader from the very first principles of the internal structure of words through to advanced issues of current controversy.